Pathogenic Microorganisms Associated With Diarrhea in Infants And Children in Duhok Province, Kurdistan Region / Iraq - Badry, Awaz H. H.; Jameel, Ahmed Y.; Mero, Wijdan M. S. (Science Journal of University of Zakho, 2014)
This study was performed to assess the incidence of microorganisms causing diarrhea in infants and children of both sexes and different ages from 12 days to 14 years in Duhok province, during the period from October 2012 to June 2013, in which 522 diarrheal samples (278 males and 244 females) were collected from infants and children attended pediatrics Heevi teaching hospital in Duhok city coming from different regions of Duhok province. Out of 522 samples 426 (81.61%) were positive for bacteria, followed by 146(27.97%) parasites, 69(13.21%) viruses and 5 (0.96%) fungi. The most prevalent enteric pathogens were Escherichia coli 305(58.43%), followed by Entamoeba histolytica 134(25.67%), Klebseilla spp. 105(20.1%), and Rotavirus 57(10.91%). Mixed infections were documented in 129 (24.71%) cases, with the maximum being with bacteria and parasite in 62(11.87%). The most frequent microorganisms encountered in mixed infections were E. coli and E. histolytica at rates of 64.34 and 62.01%, respectively. Infants less than 2 years showed the highest rate (72.22%), while children aged 12-14 years were least infected (0.96%). Moreover, the rate of infection in males was greater than females, but statistically this difference was nonsignificant.
Keywords: Microbial Diarrhea; Bacteria; Parasites; Viruses; Infants and Children